Contralateral Axillary Metastases in Breast Cancer: Stage IV Disease or a Locoregional Event?. Issue 12 (December 2019) - Guru, Swadha D.; Loprinzi, Charles L.; Yan, Elizabeth; Hoskin, Tanya L.; Jakub, James W.
Contralateral axillary metastasis (CAM) in breast cancer is presently treated as a stage IV disease. We hypothesized that this disease pattern is a manifestation of direct aberrant lymphatic drainage and would behave more similar to advanced locoregional disease. This is a single-site, retrospective review of patients with biopsy-proven CAM from 2008–2017. Descriptive analysis was performed. Twenty-three patients met the inclusion criteria. The median disease-free interval from primary tumor treatment to diagnosis of CAM was 68 months (range, 36–155 months). This population had aggressive disease (74% local recurrences and 61% clinical evidence of cutaneous or underlying muscular invasion) and extensive locoregional therapy (70% radiated, 57% mastectomy, and 65% axillary lymph node dissection) before their presentation with CAM. Fifteen (65.2%) patients recurred after treatment of CAM; the median recurrence-free interval was 11 months (range, 5–23 months), and 12 (52.2%) patients developed distant metastases. The median distant metastasis-free survival was 14 months (range, 11–23 months), and the median overall survival was 31 months (range, 22–67.5 months). Development of CAM is associated with aggressive disease and extensive prior locoregional surgery and/or radiation. The short recurrence-free interval and high progression to additional stage IV disease suggest these patients behave similar to traditional stage IV patients with resected oligometastatic disease.